We have to find x so that log (a) x= log (a) 7 + log(a) 3 - log(a) 11

Now we know that log a + log b = log ab and log a-log b = log(a/b)

log (a) x= log (a) 7 + log(a) 3 - log(a) 11

=>...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find x so that log (a) x= log (a) 7 + log(a) 3 - log(a) 11

Now we know that log a + log b = log ab and log a-log b = log(a/b)

log (a) x= log (a) 7 + log(a) 3 - log(a) 11

=> log(a) x = log(a) 7*3/11

=> log(a) x = log(a) (21/11)

Taking the antilog of both the sides we get x = 21/11.

**Therefore x = 21/11**